EKSPLORASI DAN IDENTIFIKASI JENIS TUMBUHAN OBAT DI DESA WISATA KEBUN KOPI SENARU SEBAGAI INFORMASI DASAR DALAM PENGEMBANGAN WISATA TANAMAN OBAT - Suliartini, Ni Wayan Sri; Anwar, Abdul Muta’alli; Ansori, Ahmad Alfan; Putri , Baiq Rizki Liani; Widiawati, Baiq; Syahputra, Dano; Febrian, Erni; Amal, Ihsan Itqanul; Diniatun, Mila; Mitchell, Sarah Lehani; Yanti, Yulia Kartika (Jurnal Abdi Insani, 2023)
Senaru Village is one of the villages in Bayan District, North Lombok Regency which is rich in tourist attractions. This village is included in the Rinjani Geopark area which has tropical forest gardens, waterfalls and coffee gardens. The suitability of the climate in the Rinjani Geopark complex causes this area to be rich in plant germplasm, including medicinal plants Various types of medicinal plants grow around the coffee plantation which have the potential to become medicinal plant tourism. The service is carried out by the Mataram University community empowerment service team for the 2022/2023 period. The purpose of this community service is to find out the types of medicinal plants that grow in the Senaru coffee plantation to provide education to the public about the wealth of medicinal plant germplasm that can be utilized and increase the selling value of coffee plantations as medicinal plant tourism. This program begins with collecting data on medicinal plants in the Senaru coffee plantation by exploring the types of medicinal plants that grow, photographing medicinal plants, and gathering information about the benefits of these plants. The exploration was carried out with Karang Taruna Senaru Village from 29 December 2022 – 15 January 2023. The exploration results showed a variety of medicinal plants that grow in the Senaru coffee plantation tour, including kirinyuh, horse whip, perilla Korea, jatropha, hanjuang, sig-sag, urang-aring, sembung-vine, turmeric, vanilla, pandan, galangal, porang, durian, gotu kola, jalantir, miana, chocolate and patchouli. These various types of plants have health benefits for the body. Medicinal plants found in the Senaru coffee garden are plants that grow wild or are cultivated by the community. The conclusion that can be drawn is that there is a diversity of germplasm of medicinal plants in the Senaru coffee plantation. The Senaru coffee plantation has the potential to be used as a medicinal plant tour based on the diversity of types of medicinal plants found in these tourist attractions.